Association of MicroRNA-196a2 Variant with Response to Short-Acting β2-Agonist in COPD: An Egyptian Pilot Study - Fawzy, Manal S. (PLoS One, 2016)
Chronic obstructive pulmonary disease (COPD) is a multifactorial chronic respiratory disease, characterized by an obstructive pattern. Understanding the genetic predisposition of COPD is essential to develop personalized treatment regimens. MicroRNAs (miRNAs) are small, endogenous, non-coding RNAs that modulate the expression levels of specific proteins based on sequence complementarity with their target mRNA molecules. Emerging evidences demonstrated the potential use of miRNAs as a disease biomarker. This pilot study aimed to investigate the association of the MIR-196a2 rs11614913 (C/T) polymorphism with COPD susceptibility, the clinical outcome and bronchodilator response to short-acting β(2)-agonist. Genotyping of rs11614913 polymorphism was determined in 108 COPD male patients and 116 unrelated controls using real-time polymerase chain reaction technology. In silico target prediction and network core analysis were performed. COPD patients did not show significant differences in the genotype distribution (p = 0.415) and allele frequencies (p = 0.306) of the studied miRNA when compared with controls. There were also no associations with GOLD stage, dyspnea grade, disease exacerbations, COPD assessment test for estimating impact on health status score, or the frequency of intensive care unit admission. However, COPD patients with CC genotype corresponded to the smallest bronchodilator response after Salbutamol inhalation, the heterozygotes (CT) had an intermediate response, while those with the TT genotype showed the highest response (p < 0.001). In conclusion MIR-196a2 rs11614913 polymorphism is associated with the bronchodilator response of COPD in our sample of the Egyptian population, generating hypothesis of the potential use of MIR-196a2 variant as a pharmacogenetic marker for COPD.